Epithelial lesions in prophylactic mastectomy specimens from women with BRCA mutations - Kauff, Noah D.; Brogi, Edi; Scheuer, Lauren; Pathak, Dorothy R.; Borgen, Patrick I.; Hudis, Clifford A.; Offit, Kenneth; Robson, Mark E. (Cancer, 2003)
BACKGROUND It has been suggested that BRCA‐associated breast carcinoma may often lack a detectable preinvasive phase. To investigate this hypothesis, the authors compared the prevalence of histopathologic lesions in prophylactic mastectomy (PM) specimens from women with BRCA mutations and in mastectomy specimens obtained at autopsy from an age and race‐matched comparison group without a known cancer predisposition. METHODS All specimens from women with a deleterious BRCA1 or BRCA2 mutation who participated in an ongoing follow‐up study and underwent PM at Memorial Sloan‐Kettering Cancer Center between November 1, 1987 and May 31, 2001 were reviewed. For each case, breast tissue from two age and race‐matched women without a known cancer predisposition was also reviewed. The prevalence of benign, premalignant, and cancerous lesions was compared. RESULTS Mastectomy specimens from 24 cases and 48 comparison subjects were reviewed. Ductal carcinoma in situ (DCIS), atypical ductal hyperplasia (ADH), and atypical lobular hyperplasia (ALH) were all more common in PM specimens from women with BRCA mutations than in those from the comparison group. The odds ratio for the detection of any high‐risk lesion (DCIS, lobular carcinoma in situ, ADH, or ALH) in specimens from BRCA mutation carriers was 12.7 (95% confidence interval, 3.1–52.4; P < 0.001). CONCLUSIONS Lesions associated with an increased risk of subsequent malignancy are more common in PM specimens from women with BRCA mutations than in breast tissue obtained at autopsy from unaffected women without a known predisposition. This finding suggests that hereditary breast carcinoma has a preinvasive phase that may be detectable with aggressive surveillance. Cancer 2003;97:1601–8. © 2003 American Cancer Society. DOI 10.1002/cncr.11225 Previous studies have suggested that there is a low incidence of identifiable premalignant breast lesions in women with BRCA mutations. The authors demonstrate that ductal carcinoma in situ and other proliferative lesions associated with an increased risk of subsequent malignancy are more common in prophylactic mastectomy specimens from women with BRCA mutations than in breast tissue specimens obtained at autopsy from age and race‐matched controls.